Antibiotic prescribing practices in otolaryngology head and neck surgery in Australia and New Zealand: a survey of 137 specialists - Ahmadzada, Sejad; Wong, Eugene H.; Naidoo, Yuresh (Australian Journal of Otolaryngology; Vol 2 (April 2019): Australian Journal of Otolaryngology, 2019)
Background: Antibiotic resistance has become a global health issue with substantial health and economic burdens. Surgical prophylaxis is the main indication for prescribing antibiotics and over 40% of prescriptions are inappropriate. This study aims to assess the antibiotic prescribing practices in Otolaryngology, Head and Neck Surgery in Australia and New Zealand, comparing current practices to national guidelines and current evidence. Methods: A survey was sent to practising Otolaryngologists, Head and Neck Surgeons in Australia and New Zealand. Surgeons were asked to indicate their antibiotic prescribing practises for general and subspecialty procedures. Results: A total of 472 emails were sent to members from the Australian Society of Otolaryngology, Head and Neck Surgery (ASOHNS) and New Zealand Society of Otolaryngology, Head and Neck Surgery (NZSOHNS). After 12 weeks of the survey being active, a total of 137 responses were collected (29.0% response rate). For tonsillectomy ± adenoidectomy 64% (n=87) prescribed no antibiotics while 31.1% (n=41) prescribed postoperative antibiotics. For insertion of middle ear ventilation tubes, most surgeons (51.8%, n=71) did not prescribe antibiotics while 48.9% (n=67) prescribed post-operative ototopical antibiotics only. For septoplasty ± turbinoplasty most surgeons preferred post-operative antibiotics if they used packing after the operation (62.3%, n=81). Prescribing practices for subspecialty operations within Head and Neck/Laryngology, Otology, Rhinology/Skull base and facial plastics were varied. Conclusions: Antibiotic prescribing practices were varied among Otolaryngologists, Head and Neck Surgeons in Australia and New Zealand with a gap between current prescribing practices and national guidelines. Given the increased attention to and awareness of antibiotic resistance, further high-level studies are needed to determine the need and efficacy of antibiotics in various elective operations.